Superior excursion of the humeral head: Can it be used as a prognostic tool on rotator cuff tear surgery? [Humerus başinin yukari kaymasi: Rotator kilif cerrahi̇si̇nde prognosti̇k bi̇r araç olarak kullanilabi̇li̇r mi̇?] - (:unkn) unknown (My University, 2006)
Objective: Superior excursion of the humeral head was investigated to determine whether a relationship exits between the degree of humeral head excursion and the prognosis after surgical repair. Patients and Methods: Twenty-seven patients with one sided full thickness rotator cuff tears were included in this study. The mean age was 56 (Range: 32-71) Preoperative AP x rays of both shoulders were taken. Superior excursion of the humeral head was measured. (Δe). Group A includes 0-3 mm excursion, Group B 4-5 mm. All patients underwent open cuff surgery. Constant scores were used for evaluation. Results: Supraspinatus, infraspinatus and subscapularis tears were found in 27 patients (%100), 11 patients (40.7%), and 6 patients (22.2%) respectively. 19 patients were in Group A, 8 patients were in Group B. Of the patients with supraspinatus tears (n=10), 9 of 11 patients with both supraspinatus and infraspinatus tears were in Group A. The patients with supraspinatus, infraspinatus and subscapularis tears (n=6) were all in Group B. The mean preoperative Constant Score was 48.6 in Group A, 21.5 in Group B. The mean postoperative Constant Score was 75.3 in Group A, 69 in Group B. There was a significant difference between the two groups statistically (p<0.05). A reverse relation was found to be between pre/postoperative Constant Scores and Δe. Conclusion: Superior excursion of the humeral head is an important criteria for the postoperative prognosis.
Keywords: Diagnosis; Radiograph; Rotator cuff tear; Shoulder